ROLE OF ENTEROSORPTION IN COMPREHENSIVE THERAPY FOR ACUTE RESPIRATORY DISEASES COMBINED DAMAGE TO WITH GASTROINTESTINAL TRACT DISEASE - Yu.B. Belan; M.V. Starikovich (Union of pediatricians of Russia, 2010)
The frequency of acute respiratory infections remains high in childhood. It is impossible to identify etiology most accurately in each particular case. However, according to multiple studies, viruses, their associations with each other and bacteria prevail as causative agents. In addition, it is quite often that a respiratory infection, especially in minor children, is combined with a condition of the gastrointestinal tract. Apart from symptomatic and antiviral therapies in these cases, as the authors of this article demonstrated, it is advisable to use enterosorbents. This tactics results in a decreased level of intoxication, lower intensity and duration of diarrheal syndrome, i.e. more speedy recovery.Key words: acute respiratory infections, condition of gastro tract, intoxication, diarrheal syndrome, treatment, enterosorbents, children. (Pediatric Pharmacology. - 2010; 7(3):88-90)